Deep generative AI models analyzing circulating orphan non-coding RNAs enable detection of early-stage lung cancer - Mehran Karimzadeh; Amir Momen-Roknabadi; Taylor B. Cavazos; Yuqi Fang; Nae-Chyun Chen; Michael Multhaup; Jennifer Yen; Jeremy Ku; Jieyang Wang; Xuan Zhao; Philip Murzynowski; Kathleen Wang; et al. (Nature Communications)
Abstract Liquid biopsies have the potential to revolutionize cancer care through non-invasive early detection of tumors. Developing a robust liquid biopsy test requires collecting high-dimensional data from a large number of blood samples across heterogeneous groups of patients. We propose that the generative capability of variational auto-encoders enables learning a robust and generalizable signature of blood-based biomarkers. In this study, we analyze orphan non-coding RNAs (oncRNAs) from serum samples of 1050 individuals diagnosed with non-small cell lung cancer (NSCLC) at various stages, as well as sex-, age-, and BMI-matched controls. We demonstrate that our multi-task generative AI model, Orion, surpasses commonly used methods in both overall performance and generalizability to held-out datasets. Orion achieves an overall sensitivity of 94% (95% CI: 87%–98%) at 87% (95% CI: 81%–93%) specificity for cancer detection across all stages, outperforming the sensitivity of other methods on held-out validation datasets by more than  ~ 30%.